2014
DOI: 10.1155/2014/256175
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Lyssavirus Real-Time Polymerase Chain Reaction Using Degenerate Primers with Superior Sensitivity to the Fluorescent Antigen Test

Abstract: A generic two-step lyssavirus real-time reverse transcriptase polymerase chain reaction (qRT-PCR), based on a nested PCR strategy, was validated for the detection of different lyssavirus species. Primers with 17 to 30% of degenerate bases were used in both consecutive steps. The assay could accurately detect RABV, LBV, MOKV, DUVV, EBLV-1, EBLV-2, and ABLV. In silico sequence alignment showed a functional match with the remaining lyssavirus species. The diagnostic specificity was 100% and the sensitivity proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…The viral RNA load was determined using real-time reverse transcriptase polymerase chain reaction (RT-qPCR), as described by Suin et al [36] , in the whole brain, or in the olfactory bulbs, mid (cerebrum and diencephalon) and anterior (hindbrain and cerebellum) parts of the brain. Primers recognize the nucleocapsid region of genomic RNA [36] . Previously, Suin et al [36] found a good correlation between viral RNA load and infectious virus titer in the brain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral RNA load was determined using real-time reverse transcriptase polymerase chain reaction (RT-qPCR), as described by Suin et al [36] , in the whole brain, or in the olfactory bulbs, mid (cerebrum and diencephalon) and anterior (hindbrain and cerebellum) parts of the brain. Primers recognize the nucleocapsid region of genomic RNA [36] . Previously, Suin et al [36] found a good correlation between viral RNA load and infectious virus titer in the brain.…”
Section: Methodsmentioning
confidence: 99%
“…Primers recognize the nucleocapsid region of genomic RNA [36] . Previously, Suin et al [36] found a good correlation between viral RNA load and infectious virus titer in the brain. Brain samples were homogenised using a tissue homogenizer (Bullet Blender, Next Advance, New York, USA) and 5 mm stainless steel beads in 350–1000 µl lysis buffer (RLT buffer, as supplied with Qiagen RNeasy kit, with 1% β-mercaptoethanol).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, compared to the hemi-nested RT-PCR, the established RT-qPCRs offer some important advantages in reduction of workload and run time, while providing a higher sensitivity compared to the conventional RT-PCR. Finally our assays, particularly the L-gene based assay, could be a complement for existing methods for rabies diagnosis (21,31,46,48,49) with a high specificity, sensitivity and repeatability and more suitable for broad detection of African RABV strains.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Real-time RT-PCR based assays have improved sensitivity and specificity compared to other methods, highlighting the potential of a real-time RT-PCR assay to become a leading assay for rabies laboratory diagnosis. Over the last decade many studies have been published assessing real-time RT-PCR assays for the detection of RABV and other lyssaviruses via SYBR Green or TaqMan probe [1721] methods. TaqMan probe based real-time RT-PCR assays often have lower sensitivity relative to SYBR Green based assays due to the sensitivity of TaqMan probes to the diversity of target sequences in the genomes of different RABV and other lyssaviruses [18, 2224].…”
Section: Introductionmentioning
confidence: 99%